ECMM CandiReg—A ready to use platform for outbreaks and epidemiological studies. Issue 10 (1st August 2019) - Koehler, Philipp; Arendrup, Maiken Cavling; Arikan‐Akdagli, Sevtap; Bassetti, Matteo; Bretagne, Stéphane; Klingspor, Lena; Lagrou, Katrien; Meis, Jacques F.; Rautemaa‐Richardson, Riina; Schelenz, Silke; Hamprecht, Axel; Koehler, Felix C.; et al.
Summary: Background: Recent outbreaks of Candida auris further exemplify that invasive Candida infections are a substantial threat to patients and healthcare systems. Even short treatment delays are associated with higher mortality rates. Epidemiological shifts towards more resistant Candida spp. require careful surveillance. Objectives: Triggered by the emergence of C auris and by increasing antifungal resistance rates the European Confederation of Medical Mycology developed an international Candida Registry (FungiScope™ Candi Reg) to allow contemporary multinational surveillance. Methods: Candi Reg serves as platform for international cooperation to enhance research regarding invasive Candida infections. Candi Reg uses the General Data Protection Regulation compliant data platform ClinicalSurveys.net that holds the electronic case report forms (eCRF). Data entry is supported via an interactive macro created by the software that can be accessed via any Internet browser. Results: Candi Reg provides an eCRF for invasive Candida infections that can be used for a variety of studies from cohort studies on attributable mortality to evaluations of guideline adherence, offering to the investigators of the 28 ECMM member countries the opportunity to document their cases of invasive Candida infection. Candi Reg allows the monitoring of epidemiology of invasive Candida infections, including monitoring of multinational outbreaks. Here, we describe the structure and management of the Candi Reg platform. Conclusion: Candi Reg supports the collection of clinical information and isolates to improve the knowledge on epidemiology and eventually to improve management of invasive Candida infections. Candi Reg promotes international collaboration, improving the availability and quality of evidence on invasive Candida infection and contributes to improved patient management.